2016
DOI: 10.1002/jor.23368
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 (not TLR2) dominate cognate TLR activity associated with CoCrMo implant particles

Abstract: Innate immune reactions to orthopedic implant debris are the primary cause of total joint replacement (TJR) failure over the long term (15-20 years). The role of pathogen associated pattern recognition receptors (i.e., TLRs) in regulating immune reactivity to metal implant particles remains controversial. Do different TLRs (i.e., TLR2 vs. TLR4) activated by their respective ligands in concert with metal implant debris elicit equivalent innate immune responses? In this investigation, our in vitro and in vivo da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…11 But in recent studies, PRRs, especially TLRs, have been widely reported to recognize a variety of metals from the prosthesis, such as titanium particles, cobalt ions and CoCrMo implant particles and to respond by the activation of different inflammation pathways, and then cause the secretion of proinflammatory cytokines. 8,12,13 In our previous studies, we overexpressed the small heterodimer partner (SHP), an orphan nuclear receptor that negatively regulates the TLR4/NF-κB pathway and down-regulates the P65 expression of NF-κB. The expression of NF-κB was suppressed and the expression of proinflammatory cytokines was partly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…11 But in recent studies, PRRs, especially TLRs, have been widely reported to recognize a variety of metals from the prosthesis, such as titanium particles, cobalt ions and CoCrMo implant particles and to respond by the activation of different inflammation pathways, and then cause the secretion of proinflammatory cytokines. 8,12,13 In our previous studies, we overexpressed the small heterodimer partner (SHP), an orphan nuclear receptor that negatively regulates the TLR4/NF-κB pathway and down-regulates the P65 expression of NF-κB. The expression of NF-κB was suppressed and the expression of proinflammatory cytokines was partly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the biochemical mechanisms of cobalt-induced toxicity appear to be more comprehensively characterized than those of chromium. In addition, cobalt may activate macrophages directly through TLR4 [17]. It also modifies macrophage phenotype [45] and causes strong oxidative stress [46].…”
Section: Discussionmentioning
confidence: 99%
“…Their direct cytotoxic effects can also cause tissue necrosis, which in turn may attract macrophages and lead to granulomatous responses [15] and osteolysis [16]. Cobalt may also stimulate macrophages through direct activation of Toll-like receptor 4 (TLR4) [17] and/or so-called danger signaling [18].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the many similarities between endotoxin and abrasive particles, we speculated that endotoxins participate in the biological response caused by wear particles [ 11 ]. For example, endotoxin and wear particles activate similar signal transduction pathways, increase production of prostaglandins and proinflammatory cytokines, and stimulate bone resorption.…”
Section: Introductionmentioning
confidence: 99%